2012
DOI: 10.1111/j.1365-2672.2012.05274.x
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan: antimicrobial action upon staphylococci after impregnation onto cotton fabric

Abstract: Background:  High levels of viable Staphylococcus aureus, which are often found on inflamed skin surfaces, are usually associated with atopic dermatitis. Textiles, owing to their high specific surface area and intrinsic hydrophilicity, retain moisture while also providing excellent environmental conditions for microbial growth and proliferation. Recently, a number of chemicals have been added to textiles, so as to confer antimicrobial activity. Aims:  To evaluate the antimicrobial action of chitosan upon selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 31 publications
1
29
0
Order By: Relevance
“…Samples from the antecubital crease of 24 healthy controls obtained through a previously reported research (Tavaria et al 2012) were also integrated in this study.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Samples from the antecubital crease of 24 healthy controls obtained through a previously reported research (Tavaria et al 2012) were also integrated in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The samples were cultured in Baird Parker medium (BPM; Lab M, Lancashire, UK) by spread plate technique in duplicate and incubated at 37°C during 24-48 h. The micro-organism isolation procedure was performed as described by Soares et al (2011). A total of 194 isolates were obtained from the skin of patients with AD and 48 isolates from the skin of healthy individuals, isolated and selected according to Tavaria et al (2012).…”
Section: Sample Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…"n alternative to antibiotics is curing materials with bioactive components. These dressings should ideally maintain a moist environment, act as antimicrobials to prevent secondary infections, remove exudate, and promote tissue regeneration [9,10] One group evaluated the antimicrobial action of coton textile impregnated with chitosan against bacteria isolated from the skin and found that chitosans of low-and highmolecular weight showed efective inhibition of S. aureus [11]. "nother studied the efect of chitosan in antimicrobial ultrastructural organization of clinical S. aureus strains and found changes in its cell and cytoplasmic membrane.…”
Section: Introductionmentioning
confidence: 99%